Respostas
respondido por:
0
vai dar 96º 192' 72"
99º 13' 12"
99º 13' 12"
respondido por:
1
16º 32' 12"
x 6
96º 192' 72"
Subtraindo separadamente;
72" - 60" = 12" --> este 60" que tirou vira 1' .
já tem 192' + 1' = 193'
193' - 60' =133' - 60'= 73' - 60' = 13'
Subtraímos 3 vezes o 60',logo ,se transformam
em 3º. Já tem 96º + 3º = 99º
Então o resultado fica;
16º 32' 12" x 6 = 99º 13' 12"
x 6
96º 192' 72"
Subtraindo separadamente;
72" - 60" = 12" --> este 60" que tirou vira 1' .
já tem 192' + 1' = 193'
193' - 60' =133' - 60'= 73' - 60' = 13'
Subtraímos 3 vezes o 60',logo ,se transformam
em 3º. Já tem 96º + 3º = 99º
Então o resultado fica;
16º 32' 12" x 6 = 99º 13' 12"
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás